ASSOCIATION OF ABO AND RH BLOOD GROUP TYPES TO HEPATITIS B, HEPATITIS C, HIV AND SYPHILLIS INFECTION, A FIVE YEAR' EXPERIENCE IN HEALTHY BLOOD DONORS IN A TERTIARY CARE HOSPITAL - Batool, Zufishan; Durrani, Saadia Haroon; Tariq, Shazia (Journal of Ayub Medical College Abbottabad, 2017)
Background: Aim of the study: The aim of the study was to find out the frequency of Hepatitis B Hepatitis C, Syphilis, HIV and malaria in apparently healthy blood donors and to find out any association between ABO and Rh blood groups. Methods: It was a descriptive study carried out at Rehman Medical Institute laboratory. All blood donors who volunteered for blood donation from Jan 2008 to Dec 2014 were reviewed for blood groups and screening tests. Those who were eligible were then screened for Hepatitis B, Hepatitis C, HIV, syphilis and malaria on Architect 8200i through chemiluminescent immunoassay whereas malaria was screened by a thin film. Blood group was determined by both forward and reverse grouping. Statistical analysis was carried out using SPSS software and expressed as frequencies. Results: A total of 41033 apparently healthy donors were included in the study. All of them were voluntary donors. Their age ranged from 18-70 years with a mean age of 38±10.5years. Out of these 41033, 40245 (98.3%) were males and 788(1.9%) were females. The most frequent blood group was B positive followed by O positive. Out of 41033 donors 961 (2.30%) had Hepatitis B, 566 (1.30%) had Hepatitis C, 363 (0.90%) had syphilis, 311 (0.76%) had malaria and 30 (0.07%) had HIV. There is a significant association between A blood group and HIV and hepatitis B. Donors with blood group O had no significant association with any blood transmitted infection. Conclusion: Blood group O may have some influence in protecting against blood transmitted infection. People having Blood group A are more prone to get Hepatitis B and HIV Keywords: Treponema pallidum; chemiluminescent immunoassay; Architect; Syphilis